Brain symmetry index predicts 3-month mortality in patients with acute large hemispheric infarction. Issue 47 (25th November 2022) - Liu, Lidou; Zhang, Zhe; Zhou, Yi; Pu, Yuehua; Liu, Dacheng; Tian, Jia
Abstract : Quantitative electroencephalography data are helpful to predict outcomes of cerebral infarction patients. The study was performed to evaluate the value of brain symmetry index by quantitative electroencephalography in predicting 3-month mortality of large hemispheric infarction. We studied a prospective, consecutive series of patients with large supratentorial cerebral infarction confirmed within 3 days from the onset in 2 intensive care units from August 2017 to February 2020. The electroencephalography was recorded once admission. The brain symmetry index (BSI) which is divided into BSIfast and BSIslow were calculated for each electrodes pair. The outcome was mortality at 3 months after the onset. A total of 38 patients were included. The subjects were divided into the mortality group (15 patients) and survival group (23 patients). Of the BSIfast and BSIslow at each electrodes pair, higher BSIfastC3–C4, higher BSIslowC3–C4, and higher BSIslowO1–O2 were noticed in the mortality group than that in the survival group at 3 months ( P  = .001; P  = .010; P  = .009). Multivariable analysis indicated that BSIfastC3–C4 was an independent predictor of 3-month mortality (odds ratio = 1.059, 95%CI 1.003, 1.119, P  = .039). BSIfastC3–C4 could significant predict 3-month mortality (area under curve = 0.805, P  = .005). And when we combined BSIfastC3–C4, Glasgow Coma Scale and infarct volume together to predict the 3-month mortality, the predicted value increased (area under curve = 0.840, P  = .002). BSIfastC3–C4 could independently predict the 3-month mortality of large hemispheric infarction. The combination marker which includes Glasgow Coma Scale, infarct volume, and BSIfastC3–C4 has a better diagnostic value. Further clinical trials with a large sample size are still needed.